Redefining boundaries: unveiling the schism in teacher-parent perceptions of educational engagement - Fisher, Yael; Baissberg, Shiran (Frontiers in Psychology, 2025)
IntroductionThis study explores perceptions of parental involvement among parents and teachers within the Israeli education system. The research focus is on presenting and comparing the perspectives of each group, to understand the dynamics between these two crucial stakeholders in children's education.Purpose/hypothesesThe aim of the study was to understand and compare parents' and teachers' perceptions of parental involvement in the Israeli education system. The hypothesis was that there would be differences in how these two groups view parental involvement. Examining these perceptions uncover potential areas of misalignment or conflict that might impact the effectiveness of parent-teacher collaboration.Materials and methodsThe primary methodological approach employed in this study was Facet Theory, supplemented by conventional statistical analyses. The study participants comprised 215 teachers from various schools nationwide, teaching grades 1–12, and 215 parents with children in the same grade range. To collect data, participants were asked to complete an anonymous self-report parental involvement questionnaire in which they classified parental functions based on their degree of agreement, ranging from absolute disagreement to approval and desire for such activities. This approach allowed for a comprehensive examination of parents' and teachers' perspectives across various educational levels.ResultsThe findings of this study indicate that parents' and teachers' perceptions of parental involvement differ fundamentally. Teachers' current perceptions of parental involvement were consistent with views reported in the literature three decades ago or more. They do not desire parental involvement beyond what they deem “necessary” and are averse to interference in their professional practice. According to this study's results, teachers perceive parental involvement to include the following functions: controlling school processes, participating in “obligatory” activities inherent to the parental role, and “service provision” –when needed, and they prefer that parents do not exceed the boundaries of “service provider.” Conversely, the parents' perceptions of parental involvement aligned with more recent research, which advocates for balanced parental engagement. Accordingly, parents are viewed as partners in the educational process at school, and it is believed that collaborative efforts between parents and school staff lead to improved student academic achievements. The research findings provide evidence that parents' perceptions of parental involvement consist of supporting and supplementing school resources, supervising school processes, partnership in extracurricular pedagogical processes, and maintaining awareness of internal pedagogical processes. Moreover, evidence suggests that these components relate to two loci of control: the school and its environment and the parent alone.DiscussionThe comparison between teachers' and parents' perceptions revealed significant differences; observing them can serve as a solid foundation for fostering dialogue between the two parties. This dialogue can lead to a mutual understanding and a clear, agreed-upon definition of parental involvement, paving the way for a collaborative approach between parents and teachers in the Israeli education system and ultimately promoting student success.LimitationsThis study has several limitations that should be considered when interpreting the findings, including a parent sample with higher educational attainment (83.3% holding academic degrees vs. 27.3% nationally) and predominantly female participants in both parent (86%) and teacher (93.5%) groups, which may reflect natural patterns of educational engagement but could limit broader generalizability. The online distribution method made it challenging to calculate precise response rates, and data collection during the COVID-19 pandemic may have influenced participants' perspectives on parental involvement. The findings are primarily applicable to the Israeli educational context and may require adaptation when considered in other cultural settings.